2022
DOI: 10.3390/agriculture12040469
|View full text |Cite
|
Sign up to set email alerts
|

The Changes in GABA, GAD and DAO Activities, and Microbial Safety of Soaking- and High Voltage Electric Field-Treated Adzuki Bean Sprouts

Abstract: The level of γ-aminobutyric acid (GABA) in nongerminated adzuki bean seeds is low, but it increases substantially during germination and sprouting. In this study, three seed treatments, including soaking (S), high voltage electric field (HVEF), and soaking plus HVEF (SHVEF), were used to examine their effects on sprout growth, sprout GABA content, sprout glutamate decarboxylase (GAD), and diamine oxidase (DAO) activities and microbial loads on 6-day-old adzuki bean sprouts. All the treatments enhanced sprout g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…1). For HVEF and HVEF plus soaking combination treatments, seeds were initially loaded in a polyethylene tray and placed in a chamber equipped with electrodes and a high‐voltage power supply (20 kV, 50 Hz, You‐Shang Technical Corp., Kaoshiung, City, Taiwan) (Chiu, 2022). The seeds were exposed to an electric field under strength of 4 kV cm −1 for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…1). For HVEF and HVEF plus soaking combination treatments, seeds were initially loaded in a polyethylene tray and placed in a chamber equipped with electrodes and a high‐voltage power supply (20 kV, 50 Hz, You‐Shang Technical Corp., Kaoshiung, City, Taiwan) (Chiu, 2022). The seeds were exposed to an electric field under strength of 4 kV cm −1 for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, a HVEF and H 2 O soaking combination was examined, and the result exhibited an increased germination percentage and accelerated germination speed in the treated peanut seeds in comparison with the seed receiving a single HVEF or H 2 O soaking treatment only (Table 1). Chiu (2022) reported that the HVEF treatment tended to intensify the degree of seed coat crack. These microstructural changes might further enhance the seed hydration, which were favourable for improving germination responses observed on the seeds receiving HVEF and H 2 O-soaking combination.…”
Section: Seed Treatment Effects On Germination and Sprout Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…There is rather limited information concerning PEF-derived electrochemical effects on the plant physiology and metabolic response occurring during the germination process, as pointed out by our previous review paper. 47 In a more recent research, 50 adzuki bean seeds with high voltage electric field pretreatments (2 kV/cm, 10 min) were subjected to a germination process, finding that the growth of mung bean sprouts was significantly promoted, with the length of six-day- old sprouts being 5.24 and 12.84 cm for the untreated and PEF-stressed samples, respectively. Simultaneously, PEFprestressed seeds prior to the soaking processes demonstrated significantly higher contents of GABA compared with the natural germination of seeds, but it was simply attributed to the improved activities of GAD and DAO.…”
Section: Gaba Concentration Variability Responding To Nonthermal Stre...mentioning
confidence: 99%